The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1136/thx.2006.063180
|View full text |Cite
|
Sign up to set email alerts
|

Heightened bronchial hyperresponsiveness in the absence of heightened atopy in children with current wheezing and low-income status.

Abstract: Background:Although global studies such as the International Study of Asthma and Allergies in Childhood (ISAAC) have provided valuable data on the prevalence of asthma in children in Latin America, there is little information on the relationship between asthma symptoms, pulmonary function, bronchial hyperresponsiveness (BHR) and atopy in the region. Methods: This study examined the relationship between self-reported wheezing in the past 12 months, pulmonary function, airway responsiveness and atopy in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
1
15
0
4
Order By: Relevance
“…BHR seems to represent a different pathway in the association between obesity and asthma. In a recent study of children in Latin America, BHR rather than atopy was found to be a significant risk factor for current wheezing [28]. A population birth cohort study from the UK reported significant wheezing morbidity and BHR in individuals with a history of chronic childhood atopy, particularly in males; wheezing among individuals with no history of atopy or delayed childhood atopy was found to be associated with various environmental factors such as respiratory infection, parental smoking and breast feeding [29].…”
Section: Discussionmentioning
confidence: 99%
“…BHR seems to represent a different pathway in the association between obesity and asthma. In a recent study of children in Latin America, BHR rather than atopy was found to be a significant risk factor for current wheezing [28]. A population birth cohort study from the UK reported significant wheezing morbidity and BHR in individuals with a history of chronic childhood atopy, particularly in males; wheezing among individuals with no history of atopy or delayed childhood atopy was found to be associated with various environmental factors such as respiratory infection, parental smoking and breast feeding [29].…”
Section: Discussionmentioning
confidence: 99%
“…Estas cifras son similares a lo descrito previamente por nosotros en esta misma área de Santiago 17 ; sin embargo, es más baja que la comunicada por otros autores en esta misma ciudad 16 , quienes en un estudio de 237 niños asmáticos encontraron que 62,5% tenían asma atópica. Leung en Hong Kong, en un estudio de 204 niños asmáticos de una edad promedio similar a la de nuestro grupo (8,2 años), encontró una prevalencia de TC positivo de 83%, predominantemente a ácaros del polvo de habitación 22 .…”
Section: Discussionunclassified
“…La fracción de sibilancias en los últimos 12 meses atribuible a sensibilización atópica varió desde 0% en Ankara (Turquía) a 93,8% en Guangzhou (China); también se encontró que en los países desarrollados 41% de los síntomas actuales de asma son atribuibles a la atopia. En un estudio realizado en escolares chilenos sanos y con síntomas actuales de asma, nosotros demostramos que la reactividad bronquial en niños con y sin síntomas actuales de asma puede estar aumentada sin que haya un aumento concomitante en la atopia 17 .…”
Section: Discussionunclassified
See 2 more Smart Citations